Impact of Learning Independence and Practical Tool Utilization on Outcomes in Basic Automotive Engineering - Riski Elpari Siregar; Peter Naibaho (Ali Institute or Research and Publication, 2026)
This study examines the effect of learning independence and the use of practical tools on students’ learning outcomes in the Basic Automotive Engineering subject. The research was conducted at SMK Negeri 4 Medan involving Grade X students of the Motorcycle Engineering Program. A quantitative approach with an ex post facto design was used to analyze the relationships among variables without experimental treatment. Data were collected through questionnaires to measure learning independence and practical tool usage, as well as tests to assess students’ learning outcomes. The data were analyzed using regression techniques to determine both partial and simultaneous effects. The results show that learning independence has a positive and significant influence on students’ learning outcomes. Likewise, the use of practical tools also positively affects students’ achievement. When analyzed together, learning independence and practical tool usage significantly contribute to improved learning outcomes in Basic Automotive Engineering. These findings highlight the important role of internal student factors and learning facilities in vocational education. Practically, the study suggests that teachers should encourage independent learning and maximize the use of practical tools during instruction, while theoretically it reinforces learning theories that emphasize learner autonomy and experiential learning as key determinants of academic success